Emotional awareness in the formative practice of physical education teachers - Mujica Johnson, Felipe Nicolás (2019)
A study has been carried out to identify the perception and emotional attribution of the students of Pedagogy in Physical Education during their educational practice. The methodology responds to the qualitative approach. The participants are 22 students who are in their third academic year. The data was collected through a personal diary and subjected to an inductive content analysis, using the Atlas.ti 7.5 program. The results indicate that the participants mostly perceive positive emotions for their subjective wellbeing, while the attributions emerged two central categories, named social interaction and pedagogical role. It is concluded that emotions emerge mainly due to the desire to achieve an adequate pedagogical practice, the affection received and the contribution in the learning of schoolchildren.